Partisipasi Keluarga Katolik melalui Kolekte sebagai Bentuk Kepedulian Sosial dalam Gereja Sinodal di Stasi St. Yohanes Pembaptis Wailolong - Hendrikus Boli; Petrus Tukan; Skolastika Lelu (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study examines Catholic family participation through offertory collections as a form of social concern within the Synodal Church at St. John the Baptist Wailolong Outstation. The study was motivated by the need to understand how participation in offertory collections reflects the values of communion, participation, and mission in the life of the Church. A descriptive qualitative approach was employed, involving the parish priest, the outstation council chairperson, the outstation treasurer, the Small Christian Community (KBG) leader, and Catholic parents as research participants. Data were collected through observations, interviews, and documentation and analyzed descriptively. The findings indicate that offertory collection is understood not only as a liturgical obligation but also as an expression of faith, gratitude, solidarity, and social responsibility. Family participation is demonstrated through active involvement in the Eucharistic celebration, voluntary contributions according to each family's capacity, and the early formation of children in the practice of giving. The study implies that transparent management of offertory collections strengthens trust, encourages active participation, reinforces solidarity, and promotes shared responsibility in building a Synodal Church.